Java Culture In The Qur'an Perspective (Case Study: Nyadran Culture In The Region Mt. Merapi Yogyakarta) - Nofa Nurrahma; Ahmad Rifa’i; Susilawati Susilawati (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2022)
Cultural diversity and the plurality of Indonesian society is one of the wealth of the archipelago which is a distinct characteristic of other nations. The uniqueness of Javanese culture is an interesting study to examine. Nyadran culture is one of the customs that has become a tradition in the community around Mount Merapi, Yogyakarta, namely the event of cleaning graves and sending prayers to relatives and ancestors who have died. In the Pakem area of Dusun Kledokkan Yogyakarta, the Nyadran tradition still holds a meal together in the area around the cemetery and is attended by both Muslims and non-Muslims. This research is a phenomenological research with a qualitative approach, with a literature review and field observations through interviews with local community leaders, to then be presented in a descriptive analysis. The results of this study are Nyadran is the result of acculturation of Javanese culture which is influenced by Hindu teachings and has been Islamized. This shows a gradual change in the Nyadran process, such as a party or funeral meal that has been allocated in the area outside the tomb or pavilion. There was even something held at the house of Mr. Kadus to strengthen the friendship between the family members who were buried in the tomb. In the perspective of the Qur'an, this Nyadran activity can be likened to a pilgrimage to the grave which is one of the sunnahs to remind oneself of death that is sure to come.